The Idea of the Second Lithuania in Kazys Pakštas’s Works of Independence Period - Pšibilskis, Vygintas Bronius (Lietuvos istorijos studijos, 1999)
This text describes Kazys Pakštas, a prominent Lithuanian geographer and geopolitician, who became well-known for his visionary ideas and projects, including the concept of a "spare" Lithuania. The article delves into the socio-economic factors that influenced Pakštas’ position on Lithuanian emigrants and his idea of concentrated colonization. It highlights his studies on Lithuania’s anthropological economy and overpopulation, and the solutions he proposed. Pakštas was among the first to identify key stages of Lithuanian transatlantic emigration and predicted the eventual decline of Lithuanian emigrant communities. Based on evidence from various countries, Pakštas developed the idea of planned emigration and focused colonization in countries like North and South America, Africa, and Australia. However, despite extensive research, he couldn’t pinpoint the ideal location for such a settlement. He firmly believed that creating a well-organized emigrant community in a carefully chosen location would serve as a vital reserve of Lithuanian culture and identity for the small, vulnerable nation.